Marketing planning & strategy : a practical introduction - Dawes, John (Professor of marketing) (Los Angeles : SAGE, 2021)
"This new book guides you concisely through the marketing planning process from start to finish, drawing on examples from large brands like Ikea and Krispy Kreme to digital start-ups like Starling Bank"--
Includes bibliographical references (pages 257-266) and index.
Keywords: Marketing -- Planning; Marketing -- Management